The missing links: A global study on uncovering financial network structures from partial data - Anand, Kartik; van Lelyveld, Iman; Banai, Ádám; Friedrich, Soeren; Garratt, Rodney; Hałaj, Grzegorz; Fique, Jose; Hansen, Ib; Jaramillo, Serafín Martínez; Lee, Hwayun; Molina-Borboa, José Luis; Nobili, Stefano; et al. (Journal of Financial Stability, 2018)
Capturing financial network linkages and contagion in stress test models are important goals for banking supervisors and central banks responsible for micro- and macroprudential policy. However, granular data on financial networks is often lacking, and instead the networks must be reconstructed from partial data. In this paper, we conduct a horse race of network reconstruction methods using network data obtained from 25 different markets spanning 13 jurisdictions. Our contribution is two-fold: first, we collate and analyze data on a wide range of financial networks. And second, we rank the methods in terms of their ability to reconstruct the structures of links and exposures in networks.